2018
DOI: 10.1177/1524839918783742
|View full text |Cite|
|
Sign up to set email alerts
|

Development and Evaluation of a Physician-Targeted Video to Promote HIV Screening

Abstract: Our study found that a video is an acceptable HIV testing promotion medium for physicians. Our video improved physician HIV testing knowledge and attitudes, overcoming key barriers to HIV testing.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2019
2019
2019
2019

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 21 publications
0
1
0
Order By: Relevance
“…The DISCERN instrument, developed in 1998, might be considered outdated because it was developed for rating written consumer health information and not images, videos, or other media. Educational videos have been shown to improve patient knowledge and attitudes in medicine, 38 but their utility in orthognathic surgery has largely been unstudied. Hegarty et al 39 reviewed the most popular orthognathic surgery videos on YouTube and found that 42% of videos focused on personal experiences, of which 62% described positive experiences.…”
Section: Discussionmentioning
confidence: 99%
“…The DISCERN instrument, developed in 1998, might be considered outdated because it was developed for rating written consumer health information and not images, videos, or other media. Educational videos have been shown to improve patient knowledge and attitudes in medicine, 38 but their utility in orthognathic surgery has largely been unstudied. Hegarty et al 39 reviewed the most popular orthognathic surgery videos on YouTube and found that 42% of videos focused on personal experiences, of which 62% described positive experiences.…”
Section: Discussionmentioning
confidence: 99%